Family functionality and alcohol consumption in college students - Santos Morocho, José (2018)
The present study is a transversal analysis, the objective was to determine the relationship between family functioning and alcohol consumption in a sample of 200 participants that included students of Dentistry, Nursing and Psychology. A probabilistic sampling with simple randomization was applied. The instruments used were the family evaluation test (APGAR), and the questionnaire to identify disorders due to alcohol consumption (AUDIT). The results show a significant negative relationship (p 0.211) between family functioning and alcohol consumption. Belonging to a dysfunctional family, it is a risk factor 1.21 times more likely to consume alcohol. Being part of a functional family is a protective factor for not consuming alcohol (95% CI 0.90-1.59). Regarding the variables, (33.5%) of those surveyed perceived family dysfunctions, and (48.5%) consumed alcohol within the dependent level. It is concluded that family functionality is important in order not to develop a risk behavior of alcohol consumption. Psychotherapeutic intervention is recommended to strengthen the family as a strategy to combat alcohol consumption in the university.